Analysis of Local Active Faults in Western Java from Hypocenter Relocation Using BMKG Data - Supendi, Pepen; Purbayanti, Rayi (Himpunan Ahli Geofisika Indonesia (HAGI), 2023)
We have conducted hypocenter relocation in the region of western Java that focuses on shallow depth (less than 30 km) events within a magnitude range of 2.0 to 4.9. We use a double-difference relocation method and broadband waveform data recorded by the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) regional seismic network in the western part of Java. Our results show earthquake clusters around previously unknown active faults in an area that spans the Cipamingkis fault zone, Garsela fault zone, Baribis fault zone, and an earthquake swarm in Bogor-Bayah fault zone. The dense BMKG seismic stations in the study region are particularly useful for improving the detection of small earthquake sources from local active faults. These hypocenter relocation results can be used for further seismic studies in the western Java region, such as body wave tomography and probabilistic seismic hazard analysis.